INFLUENCE OF THE DYNAMIC MODULE ON HEAT RESISTANCE OF CERAMIC COVERS OF LVM - S. A. Nikiforov (Литьë и металлургия)
Influence of the dynamic module on heat resistance of ceramic shells in casting under dispensable patterns is shown.